Amyloidogenic Propensity of a Natural Variant of Human Apolipoprotein A-I: Stability and Interaction with Ligands - Rosu, Silvana Antonia (2015)
A number of naturally occurring mutations of human apolipoprotein A-I (apoA-I) have been associated with hereditary amyloidoses. The molecular mechanisms involved in amyloid-associated pathology remain largely unknown. Here we examined the effects of the Arg173Pro point mutation in apoA-I on the structure, stability, and aggregation propensity, as well as on the ability to bind to putative ligands. Our results indicate that the mutation induces a drastic loss of stability, and a lower efficiency to bind to phospholipid vesicles at physiological pH, which could determine the observed higher tendency to aggregate as pro-amyloidogenic complexes. Incubation under acidic conditions does not seem to induce significant desestabilization or aggregation tendency, neither does it contribute to the binding of the mutant to sodium dodecyl sulfate. While the binding to this detergent is higher for the mutant as compared to wt apoA-I, the interaction of the Arg173Pro variant with heparin depends on pH, being lower at pH 5.0 and higher than wt under physiological pH conditions. We suggest that binding to ligands as heparin or other glycosaminoglycans could be key events tuning the fine details of the interaction of apoA-I variants with the micro-environment, and probably eliciting the toxicity of these variants in hereditary amyloidoses.